20th International Medical, Pharmaceutical, Cosmeceutical and Health Science Symposium - Abdullah, Noor Faradilla; Yu, Ke Xin; Balan, Santhra Segaran; Kue, Chin Siang; Mohd Yusof, Muhammad Jefri; Kumar, Suresh; Ng, Chean Hui; Tan, Seok Tyug; Sailoganathan, Ananth; Rosli, Siti Zaharah; May, Win Win; Than, Than Aye (Life Sciences, Medicine and Biomedicine, 2023)
The 20th International Medical, Pharmaceutical, Cosmeceutical & Health Science Symposium (iMPaCHS) is an annual symposium co-organized by Faculty of Life and Health Sciences, International Medical School, School of Pharmacy, Management & Science of the Management & Science University, Malaysia. With the theme 'Advancing Health Science Innovations through Interdisciplinary Collaboration', the 20th iMPaCHS aims to promote holistic research skills for future betterment. Advancing health science innovations requires a multidisciplinary approach, which involves the collaboration of experts from various fields. Interdisciplinary collaboration enables the integration of knowledge, perspectives, and methodologies from different disciplines, leading to the development of novel and effective solutions to complex health challenges. By fostering interdisciplinary collaboration, health science can leverage the strengths of each field and accelerate the translation of research findings into clinical practice, ultimately improving and advancing the overall state of health science. This is in line with the sustainable development goal and collaborative research activity in the university. The 20th International Medical, Pharmaceutical, Cosmeceutical & Health Science Symposium (iMPaCHS) is an annual symposium co-organized by Faculty of Life and Health Sciences, International Medical School, School of Pharmacy, Management & Science of the Management & Science University, Malaysia. With the theme 'Advancing Health Science Innovations through Interdisciplinary Collaboration', the 20th iMPaCHS aims to promote holistic research skills for future betterment. Advancing health science innovations requires a multidisciplinary approach, which involves the collaboration of experts from various fields. Interdisciplinary collaboration enables the integration of knowledge, perspectives, and methodologies from different disciplines, leading to the development of novel and effective solutions to complex health challenges. By fostering interdisciplinary collaboration, health science can leverage the strengths of each field and accelerate the translation of research findings into clinical practice, ultimately improving and advancing the overall state of health science. This is in line with the sustainable development goal and collaborative research activity in the university.